2018
DOI: 10.1038/s41467-018-06230-0
|View full text |Cite|
|
Sign up to set email alerts
|

Tracing the transitions from pluripotency to germ cell fate with CRISPR screening

Abstract: Early mammalian development entails transit through naive pluripotency towards post-implantation epiblast, which subsequently gives rise to primordial germ cells (PGC), the founding germline population. To investigate these cell fate transitions, we developed a compound-reporter to track cellular identity in a model of PGC specification (PGC-like cells; PGCLC), and coupled it with genome-wide CRISPR screening. We identify key genes both for exit from pluripotency and for acquisition of PGC fate, and characteri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 55 publications
(61 reference statements)
3
52
0
Order By: Relevance
“…This was rescued by transgenic Zmym2 expression. This is in agreement with a recently published Cas9 ESC differentiation screen which demonstrated that Zmym2 KO ESCs resist differentiation 25 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This was rescued by transgenic Zmym2 expression. This is in agreement with a recently published Cas9 ESC differentiation screen which demonstrated that Zmym2 KO ESCs resist differentiation 25 .…”
Section: Resultssupporting
confidence: 93%
“…We also observe that Zmym2 promotes embryonic stem cell differentiation. This has also been reported in a Cas9 screen for differentiation-promoting factors 25 . Future work could examine whether the absence of Zmym2 impacts mouse development and elucidate its role in vivo .…”
Section: Discussionsupporting
confidence: 72%
“…So far, CRISPR screen studies on mESC pluripotency or naive and primed state transition is mainly based on genetically labeled fluorescence reporters as readout (Hackett et al, 2018; Li et al, 2018; Seruggia et al, 2019), which is limited by only one or two genes. Here we employed a single-cell RNA-seq combined with CRISPR screening technology (CROP-seq) and used whole cell transcriptome as readout of cell fate changes.…”
Section: Discussionmentioning
confidence: 99%
“…ESC lines carrying floxed Dnmt1 alleles 23 and WT ESC were transfected with pPB-as Dazl sensor- Kcnq1ot1 -H2B::GFP ( in silico DNA methylated with M.SssI), pPB- EF1a -H2B::mCherry, pPB- spCas9 -Hygro 54 , and PBase using Lipofectamine 3000. Transfected cells were selected for spCas9 integration in titrated 2i/L using Hygromycin (250 μg/ml) for 5 days, and clonally-derived cell lines were subsequently isolated and expanded.…”
Section: Methodsmentioning
confidence: 99%